Exploring the Communal Pathogenesis, Ferroptosis Mechanism, and Potential Therapeutic Targets of Dilated Cardiomyopathy and Hypertrophic Cardiomyopathy via a Microarray Data Analysis - Wang, Zuoxiang; Xia, Qingyue; Su, Wenxing; Cao, Mingqiang; Sun, Yunjuan; Zhang, Mingyang; Chen, Weixiang; Jiang, Tingbo (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiomyopathies are a heterogeneous group of heart diseases that can gradually cause severe heart failure. In particular, dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM) are the two main types of cardiomyopathies, yet the independent and communal biological mechanisms of both remain far from elucidated. Meanwhile, ferroptosis is a non-apoptotic form of cell death that has been proven to be associated with cardiomyopathies, but the concrete nature of the interaction remains unclear. Hence, this study explored the pathogenesis and ferroptosis mechanism of HCM and DCM via a bioinformatics analysis. Methods Six datasets were downloaded from the Gene Expression Omnibus (GEO) database based on the study inclusion/exclusion criteria. After screening the differentially expressed genes (DEGs) and hub genes of HCM and DCM, subsequent analyses, including functional annotation, co-expression, validation, and transcription factors (TF)–mRNA–microRNA (miRNA) regulatory network construction, were performed. In addition, ferroptosis-related DEGs were also identified and verified in HCM and DCM. Results We found 171 independent DEGs of HCM mainly enriched in the regulation of ERK1 and ERK2 cascade, while 171 independent DEGs of DCM were significantly involved in cell adhesion. Meanwhile, 32 communal DEGs (26 upregulated genes and 6 downregulated genes) and 3 hub genes [periostin (POSTN), insulin-like growth factor-binding protein-5 (IGFBP5), and fibromodulin (FMOD)] were determined to be shared between HCM and DCM and the functional annotation of these genes highlighted the important position of growth hormone in HCM and DCM. Moreover, we identified activating transcription factor 3 (ATF3), lysophosphatidylcholine acyltransferase 3 (LPCAT3), and solute carrier family 1 member 5 (SLC1A5) as ferroptosis-related genes in HCM and STAT3 as a ferroptosis-related gene in DCM. Conclusion The identified independent and communal DEGs contribute to uncover a potentially distinct and common mechanism of HCM and DCM and ferroptosis-related genes could provide us with a novel direction for exploration. In addition, 3 hub genes could be potential biomarkers or therapeutic targets in patients with cardiomyopathy.